The effects of probiotics on the physiological and biochemical development of the digestive tract of commercially raised dusky kob (Argyrosomus japonicus) larvae - Hunter, Amy (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.